A Distributed Mobility Management Scheme based on Software Defined Networks - Bhalani, Nikita; Chavan, Mayur (International Journal of Computer Sciences and Engineering, 2018)
Software Defined Network is used to simplify network management by separating network control logic and forwarding mechanism which is gaining popularity as a Network in the recent years. Distributed Mobility Management is an efficient Mobility Management technique which ensures network based Mobility Management, eliminates Single Point of Failure. On the other hand, Software Defined Networks increase scalability by separating Control and Data plane unlike traditional network system. In this paper, we implement DMM scheme by distributing Control and Data plane for Mobility Management in IPv6 based networks. This scheme is expected to minimize tunneling overhead due to encryption/decryption of the data packet and minimize signaling cost. Here, we distribute both control and data plane into multiple entities and provide a suitable algorithm for selecting an appropriate agent for incoming digital Mobile Node. The performance of the selection algorithm is planning to analyze in term of handover delay, signaling costs, packet Delivery cost end to end delay and throughput.